FINDING THE HARMONY OF FINANCIAL TECHNOLOGY IN ISLAM PERSPECTIVE: A PHENOMENON IN INDONESIA - Narastri, Maulidah; Kafabih, Abdullah (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThe purpose of this article is to find out how harmony between the era of financial technology is compared with Islamic principles in Indonesia. Financial technology that is intended for humans to meet ever-increasing needs, increasingly rapid human mobilization, as well as increasing human activity. The method used in the discussion of this article is a critique of the phenomenon that developed in the era of financial technology in Indonesia as a developing country that supports the era of financial technology from developed countries. The literature used in this paper is published by national and international scientific journals and is supported by scientific books from various scientists. This article is expected to provide additional knowledge, become an opening point for further research, and be made as a guide in conducting business at various levels that discuss using financial technology. Keyword: Financial Technology, Islamic Perspective, Regulation